2022
DOI: 10.1186/s12977-022-00598-0
|View full text |Cite
|
Sign up to set email alerts
|

The key amino acid sites 199–205, 269, 319, 321 and 324 of ALV-K env contribute to the weaker replication capacity of ALV-K than ALV-A

Abstract: Background Avian leukosis virus (ALV) is an infectious retrovirus, that mainly causes various forms of tumours, immunosuppression, a decreased egg production rate and slow weight gain in poultry. ALV consists of 11 subgroups, A–K, among which ALV-K is an emerging subgroup that has become prevalent in the past 10 years. Most ALV-K isolates showed weak replication ability and pathogenicity. In this study, the weak replication ability of ALV-K was explored from the perspective of the interaction b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In general, early isolates of ALV-K exhibited no or low pathogenicity. Chen et al (13) reported that key aa sites 199-205, 269, 319, 321, and 324 of ALV-K env contributed to the weaker replication capacity of ALV-K than that of ALV-A. This is the first time that molecular factors for the weak replicative ability of ALV-K have been revealed.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In general, early isolates of ALV-K exhibited no or low pathogenicity. Chen et al (13) reported that key aa sites 199-205, 269, 319, 321, and 324 of ALV-K env contributed to the weaker replication capacity of ALV-K than that of ALV-A. This is the first time that molecular factors for the weak replicative ability of ALV-K have been revealed.…”
Section: Introductionmentioning
confidence: 92%
“…These newly discovered ALV-K strains could be adapting in the Chinese local chickens, increasing their prevalence and pathogenicity in flocks. In addition, for routine eradication and diagnostic assays, the presence of ALV-K is not easily detected due to its slow replication compared to other subgroups and the fact that it is only cultured on cells for one passage, thus making it easy to miss detection (12)(13)(14). This virus may have existed in Chinese local chickens for a long time and probably as a persistent infection without notice, due to its weak replication ability (12,14).…”
Section: Introductionmentioning
confidence: 99%
“…ALV-A and ALV-B are recognized ALV-K is the most recently characterized subgroup. It was first identified in South China in 2012 in yellow broilers and it was determined that it caused a milder disease than other subgroups [57], which may be due to decreased LTR promoter activity [58] or a weaker binding capacity of ALV-K gp85(SU) to its receptor, Tva [59]. Nucleotide sequence analysis of viruses in this subgroup shows that the gag and pol genes have high sequence similarity (>94%) to those of ALV-A through ALV-E and ALV-J (especially to those of ALV-E, 96%) [58], but may be as low as 44% for ALV-J gp37(TM), contrarily to gp85(SU), which shows low sequence similarity with that of other subgroups (<87% to ALV-A to E and <20% to ALV-J) [58,60].…”
Section: Exogenous Alv Subgroupsmentioning
confidence: 99%
“…ALV from the different subgroups tends not to cross-neutralize, except for partial cross-neutralization between subgroups B and D [94,95]. A variety of studies have identified hr1 (aa194-198 and aa206-216) and hr2 (aa251-256 and aa269-280) as the main binding domains between the viral gp85 (SU) and the host protein receptor [59,96], with vr3 contributing to the specificity of the receptor interaction for initiating efficient infection [97]. Thus, polymorphisms in hr1 and hr2 regions may determine susceptibility due to increased or decreased binding capability, with the possibility that different or new subgroups of the virus arise if the hr regions bind to a different chicken cell surface protein [21].…”
Section: The Alv Genomementioning
confidence: 99%
See 1 more Smart Citation